(untitled) - Long, Larry E. (Upper Saddle River, NJ, 1994)
Provides an overview of introductory computer and information systems concepts. Found throughout the book are web based activities which direct students to the internet. This edition is supported by a Website designed to expose students to the Internet and its information resourses. The internet bridge offers monthly Technology updates to keep the instructor and the student current with changes in this dynamic market. The internet exercises are designed to enhance students understanding and appreciation of the material in the book; introduce them to what the Internet has to offer; help them with their Internet navigation skills; show them how to find information on the Internet; show them how the internet can be used as a tool for business and personal problem solving, and help them become confident internet surfers.
Keywords: Electronic digital computers,Electronic data processing,Xử lý dữ liệu điện tử,Máy tính điện tử kỹ thuật số